Parametric study on the effect of the dielectric and geometry properties on the parasitics in gyrotron beam tunnels - Latsas, G. P.; Tigelis, I. G.; Moraitou, M. D.; Kern, S.; Vomvoridis, J. L.; Ioannidis, Z. C. (Infrared Millimeter and Terahertz Waves (IRMMW-THz), 2010 35th International Conference on, 2010)
Using the numerical code Fishbone, developed to study the parasitic oscillations in gyrotron beam tunnels, a parametric study is performed on the effect of the dielectric material as well as of the slot geometry on the growth rate of the excited parasitic modes.
Keywords: attenuation; Dielectric constant; dielectric material; dielectric materials; dielectric properties; Fishbone; Geometry; geometry properties; gyrotron beam tunnels; gyrotrons; Materials; numerical code; Oscillators; parasitic oscillations; parasitics; PLASMAS; slot geometry